Rethinking the design of resilience and adaptation indicators supporting coastal communities. Issue 12 (15th October 2022) - Keenan, Jesse M.; Maxwell, Keely
Abstract : As resilience and adaptation considerations become mainstreamed into public policy, there is an overarching desire to measure and quantify metrics and indicators that seek to evaluate the efficiency, effectiveness, and justness associated with outcomes of such processes. While much research has sought to develop specific indicators that may serve as proxies for these considerations, less research has focused on those normative aspects of indicator design that support a variety of goals associated with the accuracy, reproducibility, proxy value and multi-stakeholder translation of indicators, among various other goals and values. This perspective article sets forth a range of potential considerations that may be useful for those who seek to design and develop novel resilience and adaptation indicators ("RAIs"). These considerations are explored through a range of hypothetical examples that may be applicable to coastal communities that seek to address the practical challenges facing the design, execution, management and modification of RAIs.